Simulation Based Temperature Profiling of Human Eye due to the Exposure of LED Light (Dhaka University Journal of Science, 2022)
The use of LED luminaries is increasing day by day and the traditional sources of light are being replaced by this semiconductortechnology. In this study, the interactions of Red, Green and Blue LED light with human-eye are considered to model the temperatureprofile due to the attenuation in the ocular media. The simulation has been done using COMSOL Multiphysics 5.3. The results of thestudy show that Blue LED light causes temperature rise more than the other two colours of light. At the tip of the corneal surface,blue LED light causes the temperature to rise by 0.91⁰C whereas the rise of temperature for green and red LED are 0.85⁰C and0.46⁰C respectively. However, the temperature at the posterior layers of the eye, sclera, choroid and retina undergoes little thermaleffects due to LED light owing to the fact that the heat-flux due blood flow is dominant in that region.Dhaka Univ. J. Sci. 70(1): 34-41, 2022 (January)